2015
DOI: 10.1038/jhg.2015.5
|View full text |Cite
|
Sign up to set email alerts
|

SPTAN1 encephalopathy: distinct phenotypes and genotypes

Abstract: Recent progress in genetic analysis reveals that a significant proportion of cryptogenic epileptic encephalopathies are single-gene disorders. Mutations in numerous genes for early-onset epileptic encephalopathies have been rapidly identified, including in SPTAN1, which encodes α-II spectrin. The aim of this review is to delineate SPTAN1 encephalopathy as a distinct clinical syndrome. To date, a total of seven epileptic patients with four different in-frame SPTAN1 mutations have been identified. The major clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 53 publications
6
82
0
Order By: Relevance
“…A potential epilepsy mechanism is disinhibition of cortical pyramidal neurons merization ( Figure 6A) (4). In vitro data suggest that these mutations impair α/β spectrin complex formation (4).…”
Section: Crispr-mediated Sptan1 Deletion In Embryonic Forebrain Studmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential epilepsy mechanism is disinhibition of cortical pyramidal neurons merization ( Figure 6A) (4). In vitro data suggest that these mutations impair α/β spectrin complex formation (4).…”
Section: Crispr-mediated Sptan1 Deletion In Embryonic Forebrain Studmentioning
confidence: 99%
“…The most recent genetic study identified 20 patients with pathogenic or likely pathogenic SPTAN1 variants that exhibited a broad spectrum of neurodevelopmental phenotypes, comprising 6 patients with mild to moderate intellectual disability, with or without epilepsy and behavioral disorders, and 14 patients with EIEE, of whom 13 had severe neurodevelopmental impairment and 4 died in early childhood (5). The majority of pathological mutations discovered reside in the last 2 spectrin repeats in the C-terminal region critical for the formation of α/β spectrin heterotetramers, and some lead to aggregation of spectrin complexes in vitro (3,4). Although these observations suggest dominant-negative effects, little is known about the role of αII spectrin in brain development and the pathogenesis of EIEE5-producing SPTAN1 mutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human mutations in ␣II spectrin cause West syndrome, a severe infantile epilepsy that includes seizures, hypomyelination, and brain atrophy (Saitsu et al, 2010;Writzl et al, 2012;Tohyama et al, 2015). Mice and zebrafish lacking ␣II spectrin are embryonic and larval lethal due to cardiac and nervous system malformations (Voas et al, 2007;Stankewich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4,13 One recent article argues in favor of a dominant-negative effect in at least a subset of SPTAN1 mutations. 14 Reverse phenotyping, consisting in refining the clinical phenotype according to genetic data, allowed us to explain the recurrent malformations in our patients. In this series, we highlighted features of NPS and HHT1 disease after analyzing the gene content of the deletions.…”
Section: Discussionmentioning
confidence: 99%